2021
DOI: 10.3390/ijms221910521
|View full text |Cite
|
Sign up to set email alerts
|

Fractal-Percolation Structure Architectonics in Sol-Gel Synthesis

Abstract: It was developed a new technique to assess micro- and mesopores with sizes below a few nanometers. The porous materials with hierarchical fractal-percolation structure were obtained with the sol-gel method. The tetraethoxysilane hydrolysis and polycondensation reactions were performed in the presence of salts as the sources of metal oxides. The porous materials were obtained under spinodal decomposition conditions during application of the polymer sol to the substrate surface and thermal treatment of the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The analysis of gas sensitivity measurements based on PPD and X-ray phase analysis data allowed us to find the optimal temperature for annealing nanocomposites of a three-component system, SiO 2 –SnO 2 –In 2 O 3 (700 °C). Based on complex studies of AFM, the BET technique and on previous research [ 47 , 48 ], a hierarchical model of the formation of two-component and three-component porous nanocomposites was proposed, presented in Figure 20 and Figure 21 (in the inset, the semiconductor and dielectric grains of nanocomposites are indicated in pink and blue), accordingly. According to the AFM data, it was found that two-component porous nanocomposites, SiO 2 –SnO 2 , were macro–meso–microporous (macropore sizes of 170–180 nm and mesopore sizes of 40–50 nm) and three-component porous nanocomposites, SiO 2 –SnO 2 –In 2 O 3 , were meso–microporous (mesopore sizes of 11–15 nm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of gas sensitivity measurements based on PPD and X-ray phase analysis data allowed us to find the optimal temperature for annealing nanocomposites of a three-component system, SiO 2 –SnO 2 –In 2 O 3 (700 °C). Based on complex studies of AFM, the BET technique and on previous research [ 47 , 48 ], a hierarchical model of the formation of two-component and three-component porous nanocomposites was proposed, presented in Figure 20 and Figure 21 (in the inset, the semiconductor and dielectric grains of nanocomposites are indicated in pink and blue), accordingly. According to the AFM data, it was found that two-component porous nanocomposites, SiO 2 –SnO 2 , were macro–meso–microporous (macropore sizes of 170–180 nm and mesopore sizes of 40–50 nm) and three-component porous nanocomposites, SiO 2 –SnO 2 –In 2 O 3 , were meso–microporous (mesopore sizes of 11–15 nm).…”
Section: Discussionmentioning
confidence: 99%
“…In refs. [ 47 , 48 ], it is shown that the analytical capabilities of atomic force microscopy do not allow for the diagnosis of elements with sizes smaller than the locality of the method; therefore, the micropore system (less than 2 nm in size) cannot be detected. At the same time, the contribution of such pores to the total surface area can be determined by using the BET technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design of new material structure is a promising way to solve this problem. The most interesting approach is the development of materials with a fractal structure [17]. Fractal TiO 2 gas sensor has excellent performance in acetone detection, which attributed to the high film porosity and fractal like network structures [18].…”
Section: Introductionmentioning
confidence: 99%
“…A distinction is made among zeolites [ 32 , 33 ] based on micropore size, and the groups range from zeolites with small micropores (0.3–0.45 nm, A), through medium (0.55 nm, pentasils) and large (0.75 nm, faujasites, β—0.64 × 0.76 nm) to extra large (>0.8 nm, mordenites).…”
Section: Introductionmentioning
confidence: 99%